Antigen Specificity Enhances Disease Control by Tregs in Vitiligo - Mukhatayev, Zhussipbek; Dellacecca, Emilia R.; Cosgrove, Cormac; Shivde, Rohan; Jaishankar, Dinesh; Pontarolo-Maag, Katherine; Eby, Jonathan M.; Henning, Steven W.; Ostapchuk, Yekaterina O.; Cedercreutz, Kettil; Issanov, Alpamys; Mehrotra, Shikhar; et al. (Frontiers in Immunology, 2020)
Vitiligo is an autoimmune skin disease characterized by melanocyte destruction. Regulatory T cells (Tregs) are greatly reduced in vitiligo skin, and replenishing peripheral skin Tregs can provide protection against depigmentation. Ganglioside D3 (GD3) is overexpressed by perilesional epidermal cells, including melanocytes, which prompted us to generate GD3-reactive chimeric antigen receptor (CAR) Tregs to treat vitiligo. Mice received either untransduced Tregs or GD3-specific Tregs to test the hypothesis that antigen specificity contributes to reduced autoimmune reactivity in vitro and in vivo. CAR Tregs displayed increased IL-10 secretion in response to antigen, provided superior control of cytotoxicity towards melanocytes, and supported a significant delay in depigmentation compared to untransduced Tregs and vehicle control recipients in a TCR transgenic mouse model of spontaneous vitiligo. The latter findings were associated with a greater abundance of Tregs and melanocytes in treated mice versus both control groups. Our data support the concept that antigen-specific Tregs can be prepared, used, and stored for long-term control of progressive depigmentation.